2021
DOI: 10.1111/apha.13699
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal mesenchymal cells regulate immune responses and promote epithelial regeneration in vitro and in dextran sulfate sodium‐induced experimental colitis in mice

Abstract: Aim Disruption of the intestinal mucosal tolerance, that is, the immunological unresponsiveness to innocuous food antigens and the commensal microbiota, in the colon is associated with several chronic diseases including inflammatory bowel disease (IBD). Understanding the mechanisms responsible for intestinal mucosal tolerance has potential translational value for its therapy and management. Human intestinal mesenchymal cells (iMCs) play important roles in colonic mucosal tolerance, but further studies on their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…Overall, this published study 1 has demonstrated significant potential for iMCs to preserve epithelial integrity and dampen an inflammatory response in an animal model of severe colitis. This protective action involves down-regulating inflammation via suppressing the action of IL-1β linked to IDO-1 (although the precise mechanism of action for the latter haem protein is yet to be established as it was unclear whether protein-protein interactions or the products of IDO-1 enzymic activity were involved).…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Overall, this published study 1 has demonstrated significant potential for iMCs to preserve epithelial integrity and dampen an inflammatory response in an animal model of severe colitis. This protective action involves down-regulating inflammation via suppressing the action of IL-1β linked to IDO-1 (although the precise mechanism of action for the latter haem protein is yet to be established as it was unclear whether protein-protein interactions or the products of IDO-1 enzymic activity were involved).…”
Section: Discussionmentioning
confidence: 77%
“…In this highlighted study, 1 intestinal mesenchymal cells were sourced from human resected intestine and following enzymatic digestion isolated human cells were sub‐cultured further. Completely consistent with the study design these cultured cells exhibited a fibroblast‐like morphology while lacking haemopoietic, epithelial and endothelial markers (including CD45, CD31, EpCAM and CD 34 respectively).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Therapeutic interventions via mesenchymal cell‐macrophage crosstalk disruption have also been reported. CD45 − CD73 + CD90 + CD105 + intestinal mesenchymal cells blunted macrophage production of inflammatory cytokines in colitis 259 . Furthermore, bone marrow mesenchymal stem cells (MSC) reduced severity of colitis through secretion of TSG6, facilitating the accumulation of IL‐10‐producing macrophages 260 .…”
Section: Therapeutic Implications—from a Macrophage Perspectivementioning
confidence: 99%
“…CD45 − CD73 + CD90 + CD105 + intestinal mesenchymal cells blunted macrophage production of inflammatory cytokines in colitis. 259 Furthermore, bone marrow mesenchymal stem cells (MSC) reduced severity of colitis through secretion of TSG6, facilitating the accumulation of IL-10-producing macrophages. 260 In another work, the anticolitic role of MSCs was attributed to extracellular vesicles.…”
Section: Therapeutic Implications-from a Macrophage Perspectivementioning
confidence: 99%